A Web portal for situated Interaction - José, Rui (2004)
The combination between ubiquitous computing environments and ambient displays enables a broad range of new scenarios for situated interaction. In this paper, we describe our web based approach for situated displays. The concept of situated portal is introduced as a web portal that is targeted for presentation at a specific situation and that is based on interaction metaphors that are radically different from hypertext and oint-and-click interactions. We have created a prototype in which a situated portal is used for managing content presentation and user interaction at two different displays. This prototype has provided an important proof-of-concept and has allowed us to gain considerable feedback on its usage and scientific challenges, based on which we will now deploy a new large-scale prototype where some of the key issues will be addressed by a multi-disciplinary team.